Bundling CIS and CSA at the farm level, the case of Taita Taveta and Makueni counties in Kenya - Nduah, Alex; Karanja, Reginah; Nzuki, Esther; Ogutu, Liz (2024)
This report explores the integration of Climate Information Services (CIS) with Climate-Smart Agriculture (CSA) practices to enhance resilience among small-scale farmers in Kenya's Taita Taveta and Makueni counties. Conducted under the AICCRA project, the initiative provided training to over 1000 participants, equipping them with skills to incorporate CIS into agricultural decision-making. The program emphasized localized and timely weather information, accessible through various channels, to guide activities such as planting and irrigation. By engaging stakeholders that included farmers, agricultural officers, and private sector players such as the agro-dealers, the initiative promoted community-level adaptation strategies informed by CIS, such as crop diversification and collaborative planning. Emphasis was placed on the localized, community-centric approaches and partnerships to enhance access, adoption, and sustainability of CIS and CSA practices. Lessons learned aim to inform future CSA programs, contributing to the long-term resilience of the farming communities. The outcomes highlight the potential of bundling CIS and CSA to address climate variability and enhance agricultural productivity, offering actionable insights for scaling these efforts in future agricultural resilience programs.